2014
DOI: 10.1179/1351000214y.0000000086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PUFA-rich plant oil on risk factors of STZ-induced diabetes in Wistar rats

Abstract: These results suggest that the plant oil with high concentrations of n-6 PUFA - linoleic acid, acts prooxidatively when administered to the rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…No significant difference in lactonase activity of rat serum before and after a PUFA-rich meal has been demonstrated. Moreover, authors also found no difference in lactonase activity between the nondiabetic control without oil administration and the diabetic group (Kopál et al, 2014 ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…No significant difference in lactonase activity of rat serum before and after a PUFA-rich meal has been demonstrated. Moreover, authors also found no difference in lactonase activity between the nondiabetic control without oil administration and the diabetic group (Kopál et al, 2014 ).…”
Section: Resultsmentioning
confidence: 98%
“…Most of the research on PON1 lactonase activity has been performed on humans; however, some research groups also investigated lactonase activity in mice, rats, and cows (Farid et al, 2013 ; Kopál et al, 2014 ; Romani et al, 2009 ; Zhang et al, 2010 ). A number of studies also focused on recombinant variants of PON1 (rePON1).…”
Section: Introductionmentioning
confidence: 99%